Sexual Language Translation: The Perspective of Teaching Polite English - Putranti, Sulistini Dwi; Nababan, M R; Tarjana, Sri Samijati (IAIN Samarinda, 2018)
Students of English language can benefit their learning from translating English novels which can be found easily everywhere. Since many of those novels contain sexual languages, students need to be exposed on how to deal with taboo, vulgar and harsh languages. Â This research investigated how to produce a good and qualified translation of taboo, vulgar and harsh languages from English into Indonesian without creating pornography. The quality examined was its accuracy, acceptability and readability of the translation. The method applied in this research was descriptive qualitative with the strategy of an embedded case study. The source of data was a novel by Sandra Brown and its translation. The research reveals that the students and/or translators should handle taboo, vulgar and harsh languages found in sexual languages by applying generalization, modulation, euphemism, reduction and deletion as the techniques to translate such languages, so they are able to produce a translation which does not violate norms and values. Those techniques have proved to be able to produce a good quality translation.